Revisiting hydropotes of Nymphaeaceae. ultrastructural features associated with glandular functions - Santos Tozin, Luiz Ricardo dos [UNESP]; Rodrigues, Tatiane Maria [UNESP] (Soc Botanica Brasil, 2020)
Hydropotes are specialized epidermal structures involved in water and mineral flux into and out of the plant body. We analyzed hydropote morphology of four species of Nymphaeaceae: Nymphaea caerulea, Nymphaea lotus, Nymphaea rubra, and Victoria amazonica. Leaf samples were processed following conventional techniques for plant anatomy and for scanning and transmission electron microscopy. We observed hydropotes comprising an elongated apical sharp-pointed portion with a base composed of two to three short specialized cells. In a later developmental stage the apical sharp-pointed portion was detached and the mature hydropotes comprised an upper lens-shaped cell, a bowl-shaped cell and a large foot cell. Ultrastructural analysis revealed that the lens-shaped cell possesses labyrinthine projections in its outer periclinal wall and abundant plasmodesmata in its inner periclinal wall. Several mitochondria were present in the cytoplasm of both the lens-shaped and the bowl-shaped cells. The cytoplasm of the foot cell was reduced and possessed plastids with starch grains. The ultrastructure of the hydropotes is typical of cells involved in transporting substances and corroborates their role in the flux of substances into and out of the cell. These findings contribute to a better understanding of the functioning of hydropotes and shed light on this little-explored issue.
Keywords: Nymphaeae; subcellular features; structure; trichomes; Victoria